PENGARUH BAURAN PEMASARAN TERHADAP LOYALITAS MELALUI KEPUASAN PELANGGAN KOPERASI DI MASA PANDEMI COVID 19 - Silvia Sari (Departmen of Agribusiness, Economics and Management Faculty, Bogor Agricultural University, 2023)
Cooperatives need to increase their loyalty and customer satisfaction to be able to exist during the covid 19 pandemic. This study aims to identify and analyze the forming factors in customer satisfaction that affect cooperative customer loyalty during the covid pandemic. This research was conducted in the cities of South Tangerang and Depok. Primary data were collected through questionnaires to 100 cooperative customers using purposive sampling technique, and data analysis was performed using Structural Equation Modeling (SEM). Marketing mix (7P) as exogenous latent variable. Meanwhile, customer satisfaction and loyalty are endogenous latent variables. The results showed that based on the highest value, the promotional marketing mix factor (γ=0.26) was important to improve cooperatives in the cities of South Tangerang and Depok as a marketing strategy in maintaining customer loyalty and satisfaction during the covid 19 pandemic. recommendations for increasing promotion and physical evidence in cooperative businesses as a cooperative marketing strategy that is suitable for use during the covid 19 pandemic.